Uncovering User Experience Evaluation in Nursing-English Several platforms Through SUS and PSSUQ - Natrio, Yeyep; Malik, Rio Andika; Kasrin, Rinawati (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
The demand for English-proficient nurses in global healthcare settings has led to the development of multiple Nursing-English learning platforms. However, the user experience (UX) of these platforms significantly impacts their effectiveness in language learning. This study aims to evaluate the UX of several Nursing-English platforms using two established usability measurement tools: the System Usability Scale (SUS) and the Post-Study System Usability Questionnaire (PSSUQ). The primary objective is to uncover usability strengths and weaknesses across different platforms to improve the learning experience for nursing students. The research adopts a mixed-methods design, combining quantitative and qualitative data collection. A total of 109 nursing students from various universities in Sumatra, Indonesia, participated in this study. They were asked to use the Nursing-English platforms and evaluate them based on ease of use, system functionality, and information quality. The SUS provided an overall usability score for each platform, while the PSSUQ offered a more detailed breakdown across system usefulness, information quality, and interface quality. Results revealed an average SUS score of 84.85 across platforms, indicating a high level of user satisfaction. The PSSUQ scores corroborated these findings, with system usefulness and interface quality receiving the highest evaluations. The interactive content and relevance to nursing-specific language were highlighted as strengths, while areas for improvement included navigation and personalization features. Nursing-English platforms offer a generally positive user experience, with opportunities for optimization in user interface and learning customization. This study provides practical insights for enhancing Nursing-English learning tools to support students in preparing for global nursing careers.